Integrating Design Thinking and CBT for Mobile Telemedicine Depression Recovery Therapy for Adolescents and Women - Steffi Adam; Raymond Erz Saragih; Azizah Nur Arifah Awali (SISTEMASI, 2026)
Depression among adolescents and women has become a significant mental health issue, yet access to effective therapy remains limited due to factors such as geographical barriers and a lack of professional support. This research aims to integrate Design Thinking and Cognitive Behavioral Therapy (CBT) to develop a mobile telemedicine application, Moelih, for supporting the recovery of depression. The study employs a systematic Design Thinking approach, including Empathy, Define, Ideate, Prototype, and Test stages. The black-box testing method was employed to evaluate the app’s functionalities, ensuring that its features—such as mood tracking, journaling (both free and guided CBT), and teleconsulting with professional companions—are intuitive and effective from the user’s perspective. The results demonstrate that the Moelih app successfully meets the needs of its target audience by providing an accessible, flexible, and user-centered digital therapy tool. However, the testing phase revealed areas for improvement, such as enhancing user engagement and optimizing app responsiveness. This research highlights the potential of combining user-centered design and CBT to create effective digital interventions for mental health recovery, contributing to the growing field of telemedicine for mental health.